2 - Using Indigenous Games to Teach Problem-solving in Mathematics in Rural Learning Ecologies: by Tshele John Moloi - Moloi, Tshele John (Journal of Higher Education in Africa, 2022)
This article explores the use of morabaraba, a board game, as an example of indigenous games to teach problem-solving in mathematics. This approach is part of a rural learning ecology informed by the theory of community cultural wealth that posits community members as experts and empowers communities to find their own solutions to local issues. It is based on the existence of knowledge which learners possess but is not used in the teach- ing and learning of mathematics; there is no deficiency in the marginalized knowledge of the excluded people (Yosso 2005: 79). The author tapped into the marginalized knowledge of subaltern communities to teach problem- solving using participatory action research in generating data, hence the involvement of community members (parents, traditional leaders), education experts (teachers, mathematics subject advisors, lecturers from institutions of higher learning) and learners themselves. The primary data was generated using a tape-recorder and video camera, analysed using Van Dijk’s (2001) critical discourse analysis to identify instances of ‘discursive injustices’ in text and talk, and to acquire deeper meanings of the text. It signifies a form of resistance to unethical and unjust social power relations.